Pengolahan Air Sumur Dengan Fluidized Bed Reactor Menggunakan Media Karbon Aktif, Zeolit, Dan Kaolin - Gita Fitriani; Firra Rosariawari (Universitas Lambung Mangkurat, 2020)
The source of water that is still widely used by the community is well water, but there are still many wells that exceed the water quality standard. Like well water around Medayu, Surabaya. After testing the well water, several parameters were founds to exceed the specified clean water quality standard. These parameters are iron (Fe), manganese (Mn), lead (Pb), detergent, and KMnO4. This shows that the well water is not suitable for use. This study aims to treat well water that exceeds clean water quality standards using a fluidized bed reactor (FBR) by using media variations. The research variables are media variations (activated carbon, zeolite, and kaolin), detention time (20, 40, 60, and 80 minutes), and air pressure (2, 4, and 6 bars). The most effective results in this study are the use of zeolite as a media at a detention time of 60 minutes with an air pressure of 6 bars. Each % of parameter allowance for these results are Fe at 89,88%, Mn at 89,13%, Pb at 93,75%, Detergent at 90,74%, and KMnO4 at 95,38%.